India's manpower strategy revisited 1947-1967 - Tobias, George; Queener, Robert S. (Bombay, 1968)
INDIA has one of the longest continuous programmes of manpower strategy and action of any country developed or under developed. The book presents a comprehensive, and critical review of the man power policies and programmes as they evolved during the two decades of freedom in India. Part I of the book summarises the evolution of institutions in India dealing with various aspects of manpower planning and development. A critical appraisal of the labour force structure, educational system, training programmes and employment practices is given in Part II. In the Third and final part, key sectoral imbalances of manpower supply and demand are analysed and new directions of manpower strategy are indicated. After describing and evaluating the manpower strategy of India during the last 20 years, the authors offer guidelines for successful manpower planning and for better utilisation of manpower. The book contains a wealth of data including a statistical appendix.
Keywords: Forced labor, Manpower